The development of students' cultural awareness through an Indonesian cross-cultural counseling - Fadhilla Yusri; Yeni Afrida (Jurnal Konseling dan Pendidikan, 2024)
The research was motivated by the difficulties of prospective counselors in understanding the culture of origin of their counselee in cross-cultural counseling practices. The research aims to increase the cultural awareness of prospective counselors towards the counselee they help. This type of research is action research carried out through three cycles, namely, 1) prospective counselors understand the counselee’s culture from expert who have a different cultural background from the counselee, 2) prospective counselors understand the counselee’s culture from peers who have a different background from the counselee, and 3) prospective counselors understand the culture of individual who were born and raised in the counselee’s culture. The population in the research was 110 students from the BK UIN Bukittinggi department studying cross-cultural counseling. Samples were drawn using the accidental techniques as many as 40 people. The research data were processed using difference test (t-test). The results of the research reveal that prospective counselors understand the counselee culture more easily than individuals who were born and raise in the counselee culture. The result of this research recommend using sources from the culture origin to increase prospective counselors awareness of the counselee’s culture in cross-cultural counseling.